Luminescence of Eu(III) beta-diketone complex supported on functionalized macroporous silica matrix - Sigoli, F. A.; Brito, H. F.; Jafelicci, M.; Davolos, Marian Rosaly [UNESP] (Elsevier B.V., 2001)
This work reports on the photoluminescent properties of the complex diequatris(thenoyltrifluoroacetonate) europium(III), which was adsorbed or supported on tubes of modified surface silica matrix. The luminescence data and the experimental intensity parameter results evidence the existence of high interactions between the complex [Eu(tta)(3)(H2O)(2)] and the modified surface matrix. The anchored complex on macroporous silica shows higher intensity parameter values suggesting that the Eu-0 bond becomes more covalent than the adsorbed one. Therefore, the hypersensitive character of the D-5(0) --> F-7(2) transition increases evidencing a high contribution of the dynamic coupling mechanism possibly due to highly polarizable chemical environments occupied by europium(III) ion. The lifetimes of the complex on silica matrices were measured. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: luminescence; silica; macroporous matrix; lanthanide complexes; europium; thenoyltrifluoroacetonate